Hyers-Ulam and Hyers-Ulam-Rassias stability of a class of integral equations on finite intervals - Simões, A. M. (2018)
The purpose of this work is to study different kinds of stability for a class of integral equations defined on a finite interval. Sufficient conditions are derived in view to obtain Hyers-Ulam stability and Hyers-Ulam-Rassias stability by using fixed point techniques and the Bielecki metric.